Pengaruh Financial Knowledge, Financial Attitude dan Self Control terhadap Perilaku Menabung Siswa Kelas XI SMAN 1 Wringinanom - Riska Firdatus Samadiyah, Nur; Nersiwad, Nersiwad; Verlandes, Yuliasnita (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Saving behavior is an important aspect in individual financial management. This study aims to investigate how financial knowledge, attitudes towards finances, and self-control influence saving behavior in class XI students at SMAN 1 Wringinanom. This type of research is quantitative. The population studied was all class XI students of SMAN 1 Wringinanom, totaling 400 students. A sample of 80 students was selected using the Slovin formula method and purposive sampling. Data was collected through the use of questionnaires, and data analysis was carried out using multiple linear regression with the help of the SPSS version 27 application for Windows. The results of the research show that the financial knowledge variable has a positive and significant influence on saving behavior, financial attitude has a positive and significant influence on saving behavior, and self-control has a positive and significant influence on saving behavior as well as the financial knowledge, financial attitude and self-control variables. simultaneously have an influence on saving behavior.